Competition and conversion between pnicogen bonds and hydrogen bonds involving prototype organophosphorus compounds. Issue 34 (20th August 2021) - Jing, Xinyue; Zeng, Yanli; Zhang, Xueying; Meng, Lingpeng; Li, Xiaoyan
Abstract : The properties of pnicogen bonds and hydrogen bonds involving prototype organophosphorus compounds (RPO2 ) and their conversion mechanisms have been investigated. Abstract : Ab initio calculations have been performed to investigate the competition and conversion between the pnicogen bonds and hydrogen bonds in complexes containing prototype organophosphorus compounds RPO2 (R = CH3 and CH3 O). The competition between the pnicogen bonds and hydrogen bonds is controlled by the magnitude of V s, min and V s, max in the prototype organophosphorus compounds. Monomeric methyl metaphosphate (CH3 OPO2 ), with more positive π-holes, is more likely to form pnicogen bonds with different electron donors, such as NH3, H2 O, HNC and HCCH. Methoxyphosphinidene oxide ( trans - and cis -CH3 OPO) is inclined to form hydrogen bonds with H2 O, HNC and HCCH. Most of the pnicogen bonds have covalent or partially covalent character, while most of the hydrogen bonds exhibit the noncovalent characteristics of weak interactions. The mechanisms of three typical conversions between the pnicogen bond and the hydrogen bond have been investigated and the breakage and formation of the bonds along the reaction pathways have been analyzed using topological analysis of electron density. For the three studied conversion processes, the transformation between the hydrogen-bonded complex and pnicogen-bonded complex is achieved readily through several T-shape structure transition states.